Novel pathogenic EIF2S3 missense variants causing clinically variable MEHMO syndrome with impaired eIF2γ translational function, and literature review. Issue 5 (4th September 2020) - Kotzaeridou, Urania; Young‐Baird, Sara K.; Suckow, Vanessa; Thornburg, Alexis G.; Wagner, Matias; Harting, Inga; Christ, Stine; Strom, Tim; Dever, Thomas E.; Kalscheuer, Vera M.
Abstract: Rare pathogenic EIF2S3 missense and terminal deletion variants cause the X‐linked intellectual disability (ID) syndrome MEHMO, or a milder phenotype including pancreatic dysfunction and hypopituitarism. We present two unrelated male patients who carry novel EIF2S3 pathogenic missense variants (p.(Thr144Ile) and p.(Ile159Leu)) thereby broadening the limited genetic spectrum and underscoring clinically variable expressivity of MEHMO. While the affected male with p.(Thr144Ile) presented with severe motor delay, severe microcephaly, moderate ID, epileptic seizures responsive to treatments, hypogenitalism, central obesity, facial features, and diabetes, the affected male with p.(Ile159Leu) presented with moderate ID, mild motor delay, microcephaly, epileptic seizures resistant to treatment, central obesity, and mild facial features. Both variants are located in the highly conserved guanine nucleotide binding domain of the EIF2S3 encoded eIF2γ subunit of the heterotrimeric translation initiation factor 2 (eIF2) complex. Further, we investigated both variants in a structural model and in yeast. The reduced growth rates and lowered fidelity of translation with increased initiation at non‐AUG codons observed for both mutants in these studies strongly support pathogenicity of the variants. Abstract :